UMPSA Kembara Prihatin visits Semporna community - Mimi Rabita, Abdul Wahit (UMPSA, 2023)
SEMPORNA, 31 July 2023 - A total of 27 volunteers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) among staff, alumni, Yayasan UMP Squad and Rakan Siswa YADIM succeeded in benefiting residents on Pulau Bum Bum, especially in Kampung Balimbang, Berjasa, Samal Samal and Berjaya.